Comparative study of vaginal misoprostol and intra cervical Foley’s catheter for pre-induction cervical ripening at term - Agarwal, Meghna; Kose, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: At times of unfavorable cervix induction of labor with cervical ripening agents were necessary. The present study was done to compare the efficacy and outcome of vaginal misoprostol and Foleys catheter in pregnant women for induction of labor. Methods: This randomized clinical trial was performed on 10o pregnant women during a time period of December 2014 to November 2016. These women were randomly divided into two groups: Misoprostol (50 patients) and Foley catheter (50 patients). For the first group, 25 mcg vaginal misoprostol was administered every 4 h up to maximum of 3 doses for a period of 12 hours. For the second group, Foley catheter 18 F, was placed through the internal os of the cervix. Data was analyzed using SPSS software 20. p <0.05 was considered statistically significant. Results: The mean age of the patients in Group 1 was 24.72±2.93 years and Group 2 was 24.12±2.88 years. Pre-induction & post-induction modified Bishop score was significantly higher in Group 1 (Misoprostol) as compared to Group 2 (Foley’s catheter) in primigravida and multigravida patients. The difference in the birth weight and Apgar score at 1 min and 5 min between the two groups was statistically not significant (p>0.05). The rate of vaginal delivery was significantly more in Misoprostol group as compared to Foley’s catheter group (p<0.05). The caesarean section rate was more in Foley’s catheter group as compared to Misoprostol group and the results were statistically significant (p<0.05). Conclusions: It was concluded that misoprostol decrease the delivery time and increases the vaginal delivery compared to Foleys catheter.